Activity pattern of the neotropical marsupial Didelphis aurita in south-eastern Brazilian Atlantic Forest. (6th February 2014) - Ferreira, Mariana Silva; Vieira, Marcus Vinícius
Abstract: Nocturnal activity is generally presumed, but rarely evaluated in studies of tropical small mammals. When evaluated, activity is frequently presented as a fixed pattern, but actually it is the influence of biotic and abiotic factors on individuals. We investigated effects of age, sex, minimum temperature, reproductive and climatic seasons on activity of Didelphis aurita (Didelphimorphia, Didelphidae) in an Atlantic Forest area in south-eastern Brazil from June 2009 to December 2010. We captured 37 individuals, 51 times (28 females and 23 males). Activity of D. aurita was mostly nocturnal, but some individuals were active during the day (12%, N = 6). Nocturnal activity was bimodal, more prevalent in adults than juveniles, and different from most neotropical marsupials. Contrary to expectations, individuals of D. aurita were more active at colder temperatures, which indicates that low temperatures do not limit foraging behaviour.